2019
DOI: 10.3390/app9010171
|View full text |Cite
|
Sign up to set email alerts
|

Landslide Susceptibility Modeling Using Integrated Ensemble Weights of Evidence with Logistic Regression and Random Forest Models

Abstract: The main aim of this study was to compare the performances of the hybrid approaches of traditional bivariate weights of evidence (WoE) with multivariate logistic regression (WoE-LR) and machine learning-based random forest (WoE-RF) for landslide susceptibility mapping. The performance of the three landslide models was validated with receiver operating characteristic (ROC) curves and area under the curve (AUC). The results showed that the areas under the curve obtained using the WoE, WoE-LR, and WoE-RF methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 122 publications
2
96
1
1
Order By: Relevance
“…AdaBoost, random forest and bagging are some of the random subspaces used in ensemble models. These techniques have now been utilized for groundwater potential analysis, landslide and flood susceptibility analysis (Chen et al 2019) [18]. In AdaBoost model inaccuracy arises as it ignores the remaining data by concentrating on the difficult one which leads to a large range of diversity in the performance of bagging [94].…”
Section: Bagging Ensemble Classifiermentioning
confidence: 99%
See 1 more Smart Citation
“…AdaBoost, random forest and bagging are some of the random subspaces used in ensemble models. These techniques have now been utilized for groundwater potential analysis, landslide and flood susceptibility analysis (Chen et al 2019) [18]. In AdaBoost model inaccuracy arises as it ignores the remaining data by concentrating on the difficult one which leads to a large range of diversity in the performance of bagging [94].…”
Section: Bagging Ensemble Classifiermentioning
confidence: 99%
“…Although domain-knowledge-driven qualitative approach is advantageous in predicting landslides, data-driven quantitative methods are widely used because collecting field data from landslide areas are challenging and hard to acquire [3]. Pourghasemi et al [14] reported that a variety of quantitatively-statistical, multi-criteria decision making, and machine learning-methods have been applied for predicting landslide susceptibility, of which logistical regression [15][16][17][18] is the most frequently used method, followed by the frequency ratio [19,20], weights-of-evidence [18,21], artificial neural networks [22,23], analytic hierarchy process [24,25], statistical index [26], index of entropy [27][28][29][30], and support vector machine [31,32]. Environmental data collected from fields as well as extracted from satellite images to develop landslide prediction models are diverse in nature, and therefore prone to inaccuracies [13].…”
Section: Introductionmentioning
confidence: 99%
“…The study area has ten lithology types ( Figure 2l). Lithology is also considered as an important landslide-related factor in landslide susceptibility mapping [90]. The variation of lithology may lead to the variation of strength and permeability of rock stratum.…”
Section: Landslide Conditioning Factorsmentioning
confidence: 99%
“…Chen et al [8] in their paper titled "Landslide Susceptibility Modeling Using Integrated Ensemble Weights of Evidence with Logistic Regression and Random Forest Models" employed the integrated ensemble WoE with logistic regression (LR) and RF models to map landslide susceptibility and quantitatively compared and analyzed by receiver operating characteristic (ROC) curves and AUC.…”
Section: Machine Learning Techniques and Their Applicationsmentioning
confidence: 99%